Low‐dielectric silylbutylene‐benzocyclobutene resin with photoactive silacyclobutane groups via acyclic diene metathesis polymerization. (29th April 2022) - Fan, Li; Cao, Ke; Hu, Huan; Ma, Jiajun; Peng, Qiuxia; Li, Xian; Huang, Yawen; Yang, Junxiao
Abstract: UV‐curable resins with low dielectric constant can be processed or patterned to form required shapes, making them highly applicable to special fields. In our previous study, UV‐curable siloxane‐benzocyclobutene resins were synthesized, but their dielectric constants were relatively high. In this work, silylbutylene‐benzocyclobutene oligomers (ADM‐PBSC) were synthesized by acyclic diene metathesis (ADMET) polymerization of 1, 1‐dibutenylsilacyclobutane monomers with benzocyclobutene terminated groups. In this way, siloxane moieties were replaced by silylbutylene groups to further reduce dielectric constant while preserving UV curable properties. The UV/thermally cured ADM‐PBSC exhibited good mechanical properties and high thermal stability. Furthermore, the cured resins showed low dielectric constants (2.49 at 10 MHz) and low dielectric losses (10 −3 at 10 MHz). Good comprehensive properties of ADM‐PBSC may be attributed to its UV/thermally dual cross‐linked structure.